Traditional clinical outcomes in prelicensure nursing education: an empty systematic review - Leighton, Kim; Kardong-Edgren, Suzan; McNelis, Angela M.; Foisy-Doll, Colette (My University, 2021)
Background: Effectiveness of traditional apprenticeship models used in undergraduate nursing education has been questioned in the literature for over 50 years. This systematic review aimed to examine best evidence available upon which to base decisions regarding use of traditional clinical experience with prelicensure nursing students. Method: A systematic review was conducted following Joanna Briggs Institute and Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Nine electronic databases were searched. Full-text review was completed for 118 articles meeting inclusion criteria. Results: No studies reported learning outcomes attributed to clinical education models, resulting in an empty review. Studies were commonly self-reports of perceptions and confidence, lacking quantitative outcomes. Conclusion: No sufficient evidence was found to support traditional clinical models. The scope of nursing practice and patient complexity requires higher order thinking skills, ability to prioritize, and leadership in interdisciplinary care environments. This review raises serious concerns about how nurse educators assess learning in traditional clinical environments.
Keywords: undergraduate nursing education; traditional clinical experience